2013
DOI: 10.1038/labinvest.2013.77
|View full text |Cite
|
Sign up to set email alerts
|

PepT1 expressed in immune cells has an important role in promoting the immune response during experimentally induced colitis

Abstract: We and others have shown that the dipeptide cotransporter PepT1 is expressed in immune cells, including macrophages that are in close contact with the lamina propria of the small and large intestines. In the present study, we used PepT1-knockout (KO) mice to explore the role played by PepT1 in immune cells during dextran sodium sulfate (DSS)-induced colitis. DSS treatment caused less severe body weight loss, diminished rectal bleeding, and less diarrhea in PepT1-KO mice than in wild-type (WT) animals. A histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 54 publications
2
35
1
Order By: Relevance
“…These results suggest that bacteria and/or bacterial products play an important role in the exacerbation of DSS-induced colitis in mice and further suggest that miR-193a-3p is crucial for regulating PepT1-mediated bacterial products in inducing intestinal inflammation. These data are consistent with a recent work demonstrating that knocking down the PepT1 expression decreases chemotaxis of immune cells recruited during intestinal inflammation, which is dependent on bacteria and/or bacterial products (34). miRNAs can modulate cellular activities through the regulation of extensive gene networks and may exert different functions that depend on the cellular context (41).…”
Section: Mir-193a-3p Reduces Intestinal Inflammationsupporting
confidence: 92%
“…These results suggest that bacteria and/or bacterial products play an important role in the exacerbation of DSS-induced colitis in mice and further suggest that miR-193a-3p is crucial for regulating PepT1-mediated bacterial products in inducing intestinal inflammation. These data are consistent with a recent work demonstrating that knocking down the PepT1 expression decreases chemotaxis of immune cells recruited during intestinal inflammation, which is dependent on bacteria and/or bacterial products (34). miRNAs can modulate cellular activities through the regulation of extensive gene networks and may exert different functions that depend on the cellular context (41).…”
Section: Mir-193a-3p Reduces Intestinal Inflammationsupporting
confidence: 92%
“…TNFR2 signaling mediates the activation of MLCK and the change in localization of occludin. TNFR2 signaling also induces infiltration of macrophages and neutrophils into the lamina propria and activates Th17 cells (50,51). Su et al (20) reported that the induced expression of TNFR2 in murine colitis promoted apoptosis of intestinal epithelial cells, chemokine overexpression, and exacerbation of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Colitis was induced by the addition of 3% (w/v) dextran sodium sulfate (DSS; molecular weight 36,000–50,000 Da; MP Biomedicals, LLC, OH) to the drinking water [9]. Physical characteristics such as body weight and pro and anti-inflammatory cytokine profile were matched with previously reported [10].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a polymorphism of the hPepT1 gene has been shown to be associated with IBD susceptibility, indicating a direct involvement of this transporter in IBD [8]. Also, it has been shown that PepT1 expressed in immune cells played an important role in promoting the immune response during experimentally induced colitis compared to the knock-out mice [9]. Recent study showed that IL-16 induces intestinal inflammation by up regulating PepT1 expression in puffer fish intestine and it subsequently transported the bacterial peptide fMLP which triggers the intestinal inflammation [7].…”
Section: Introductionmentioning
confidence: 99%